Recent Trends of Laparoscopic Surgery in National Hospitals. (II). Endoscopic Surgery of Mammary Gland and Thyroid Diseases - FURUTA Kazunori; ASATO Yutaka; SHIMOYAMA Yutaka; SAKATA Michio; MIYABE Rika (Japanese Journal of National Medical Services, 1999)
The advantages of endoscopic axillary lymphnode resection are no incision of axillary deep pectoral fascia, no post operative axillary drawn, good recovery of shoulder joint movement, a slight pain for rehabilitation compared with conventional breast cancer operation. Postoperative axillary wound in not be conspicuous, and this procedure has possibility as reduce postoperative hospital days. Complication of this operation sometimes happened pneumohypoderma.Conventional operation of any thyroid diseases have large skin incision of anterior cervical area, and operative scar are conspicuous places. But endoscopic thyroidectomy have complete covered operative scar with clothes. Complication of recurrence nerve injury will be able to prevent under endoscopic thyroidectomy. Because endoscopic thyroidectomy have a good magnified visualization. At present, this operations take a long time. Subject of endoscopic thyroidectomy is shortage of operation time.Both of endoscopic surgery will be able to become short operation time and extend operative indication, if become proficient in technique, device of procedure, development of operative compliments. 我々の行っている乳癌に対する内視鏡下腋窩リンパ節郭清術の最大の利点は, 従来法の手術に比べて, 腋窩の深胸筋膜の切開を行わず, 術後の腋窩のひきつれがなく, 肩関節の可動域の回復が非常に良好であり, リハビリテーションによる癒痛が軽いことである. また, 腋窩の傷が目立たず, 入院期間の短縮が可能であるなどである. 問題点として, 保険適応が現在のところない. 小範囲であるが, 皮下気腫が生じるなどがある.内視鏡下甲状腺切除術については, 利点としては従来の手術では, 疾患によらず, 前頚部の皮膚切開は両側に広範囲になることが多く, 手術瘢痕は人目に付きやすい. 内視鏡下手術では手術創は完全に下着によって被覆される. 合併症で反回神経の損傷についても, 内視鏡下手術では, 良好な拡大視野のために, 反回神経損傷は最小限に抑えられる. 今後の課題は, 手術時間の短縮である.これら内視鏡下手術とも手術に対する習熟や手技の工夫, 手術器具の開発がなされることで, 他の内視鏡下手術と同様に手術時間の短縮とともに今後, 適応の拡大がはかれると思われる.